(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
In 1820, French naturalist August Saint Hillaire, during a visit in Espírito Santo (ES), a state in southeastern Brazil, reported a popular use of Cyperaceae species as antidote to snake bites. The plant may even have a hypotensive effect, though it was never properly researched. The in vitro inhibitory of the angiotensin converting enzyme (ACE) activity of eigth ethanolic extracts of Cyperaceae was evaluated by colorimetric assay. Total phenolic and flavonoids were determined using colorimetric assay. The hypotensive effect of the active specie (Rhychonospora exaltata, ERE) and the in vivo ACE assay was measured in vivo using male Wistar Kyoto (ERE, 0.01-100mg/kg), with acetylcholine (ACh) as positive control (5 µg/kg, i.v.). The evaluation of ACE in vivo inhibitory effect was performed comparing the mean arterial pressure before and after ERE (10 mg/kg) in animals which received injection of angiotensin I (ANG I; 0,03, 03 and 300 µg/kg, i.v.). Captopril (30 mg/kg) was used as positive control. Bulbostylis capillaris (86.89 ± 15.20%) and ERE (74.89 ± 11.95%, ERE) were considered active in the in vitro ACE inhibition assay, at 100 µg/mL concentration. ACh lead to a hypotensive effect before and after ERE's curve (-40±5% and -41±3%). ERE showed a dose-dependent hypotensive effect and a in vivo ACE inhibitory effect. Cyperaceae species showed an inhibitory activity of ACE, in vitro, as well as high content of total phenolic and flavonoids. ERE exhibited an inhibitory effect on both in vitro and in vivo ACE. The selection of species used in popular medicine as antidotes, along with the in vitro assay of ACE inhibition, might be a biomonitoring method for the screening of new medicinal plants with hypotensive properties.